Severe and Frequent Loneliness Mars Adults with Hearing Loss : Loneliness Mars Adults with Hearing Loss - Irum, Aqsa; Mumtaz, Nazia; Saqulain, Ghulam; Asghar, Amna; Dawood, Tayyaba (Pakistan Journal of Health Sciences, 2023)
There is a high prevalence of hearing loss in community and need of research to address this gap into the health-related issues of hearing loss like loneliness, anxiety and depression, hence current study was conducted. Objective: To determine the subjective loneliness in adults with hearing loss and association with clinico-demographic variables. Methods: This cross-sectional study was conducted at Isra University Islamabad, recruited N=377 patients with hearing loss utilizing convenience sampling from Sir Ganga Ram and Mayo Hospitals, Lahore, Pakistan from January 2020 to June 2020. The sample included both genders, aged 20 to 65 years with moderate to profound hearing loss of at least 1-year duration. The basic demographic sheet and University of California, Los Angeles (UCLA) Loneliness Scale Version 3 were used for data collection. Data were analyzed using SPSS Version 26 & Chi-square was utilized for association with p<0.05 taken to be significant. Results: Study revealed severe loneliness in 279(74%) and frequent loneliness in 98(26%). Severity categories of loneliness revealed association with age (p=0.049), gender (p=0.043), smoking (p=0.049), type of hearing loss (p<0.001), degree of hearing loss (p=0.008), hearing aid use (p<0.001), hours and days of hearing aid use (p<0.001). Conclusions: It is concluded that hearing loss results in severe and frequent loneliness. Factors including age, gender, smoking, type of hearing loss, degree of hearing loss, hearing aid use, hours and days of hearing aid use are associated with loneliness in adult population of Punjab, Pakistan.